(untitled) (Journal of Educational Sciences, 2017)
The article highlights the issues of intraschool management of a small-scale (rural) school. The results of a project study of the article authors on the topic «Интеграция сельских ресурсных центров и самостоятельных малокомплектных школ в единый образовательно-информационный технопарк (опорная школа на базе вуза)» («Integration of rural resource centers and independent small-scale schools into a single educational and information technology park (a basic school on the basis of a university)») are reflected. Some aspects of the effective activity of the school are identified on the basis of the modern theory of innovation management, which ensures the change of influence philosophy in school management to the philosophy of interaction, cooperation and maximum participation of allmembers of the team in this process. A generalized analysis of the network of small-scale schools in the country and a contingent of students in them is presented. The activities of the basic school (resource center) are considered, on the basis of which the educational resources for short-term in-session lessons,intermediate and final certification of students are consolidated in order to provide access to quality education for students in rural remote locations. The results of cooperation with Austrian colleagues are displayed, their experience of working in schools similar to ours, mainly located in rural areas, is described.The practical significance of the research is that the authors present material for the organization of scientifically based management of small-scale schools. Key words: small staffing school, resource center, management of education.